Extracorporeal treatment for theophylline poisoning: Systematic review and recommendations from the EXTRIP workgroup. (May 2015) - Ghannoum, Marc; Wiegand, Timothy J.; Liu, Kathleen D.; Calello, Diane P.; Godin, Melanie; Lavergne, Valery; Gosselin, Sophie; Nolin, Thomas D.; Hoffman, Robert S.; ,
Abstract: Background . The Extracorporeal Treatments in Poisoning workgroup was created to provide evidence-based recommendations on the use of extracorporeal treatments (ECTRs) in poisoning. Here, the workgroup presents its systematic review and recommendations for theophylline. Methods . After a systematic review of the literature, a subgroup reviewed articles, extracted data, summarized findings, and proposed structured voting statements following a pre-determined format. A two-round modified Delphi method was chosen to reach a consensus on voting statements and the RAND/UCLA Appropriateness Method was used to quantify disagreement. Anonymous votes were compiled, returned, and discussed. A second vote determined the final recommendations. Results . 141 articles were included: 6 in vitro studies, 4 animal studies, 101 case reports/case series, 7 descriptive cohorts, 4 observational studies, and 19 pharmacokinetic studies, yielding a low-to-very-low quality of evidence for all recommendations. Data on 143 patients were reviewed, including 10 deaths. The workgroup concluded that theophylline is dialyzable (level of evidence = A) and made the following recommendations: ECTR is recommended in severe theophylline poisoning (1C). Specific recommendations for ECTR include a theophylline concentration [theophylline] > 100 mg/L (555 μmol/L) in acute exposure (1C), the presence of seizures (1D), life-threatening dysrhythmias (1D) or shock (1D), a rising [theophylline] despite optimal therapy (1D), and clinical deterioration despite optimal care (1D). In chronic poisoning, ECTR is suggested if [theophylline] > 60 mg/L (333 μmol/L) (2D) or if the [theophylline] > 50 mg/L (278 μmol/L) and the patient is either less than 6 months of age or older than 60 years of age (2D). ECTR is also suggested if gastrointestinal decontamination cannot be administered (2D). ECTR should be continued until clinical improvement is apparent or the [theophylline] is < 15 mg/L (83 μmol/L) (1D). Following the cessation of ECTR, patients should be closely monitored. Intermittent hemodialysis is the preferred method of ECTR (1C). If intermittent hemodialysis is unavailable, hemoperfusion (1C) or continuous renal replacement therapies may be considered (3D). Exchange transfusion is an adequate alternative to hemodialysis in neonates (2D). Multi-dose activated charcoal should be continued during ECTR (1D). Conclusion . Theophylline poisoning is amenable to ECTRs. The workgroup recommended extracorporeal removal in the case of severe theophylline poisoning.